Senecavirus A as an Oncolytic Virus: Prospects, Challenges and Development Directions - Luo, Dankun; Wang, Haiwei; Wang, Qiang; Liang, Wenping; Liu, Bo; Xue, Dongbo; Yang, Yang; Ma, Biao (Frontiers in Oncology, 2022)
Oncolytic viruses have the capacity to selectively kill infected tumor cells and trigger protective immunity. As such, oncolytic virotherapy has become a promising immunotherapy strategy against cancer. A variety of viruses from different families have been proven to have oncolytic potential. Senecavirus A (SVA) was the first picornavirus to be tested in humans for its oncolytic potential and was shown to penetrate solid tumors through the vascular system. SVA displays several properties that make it a suitable model, such as its inability to integrate into human genome DNA and the absence of any viral-encoded oncogenes. In addition, genetic engineering of SVA based on the manipulation of infectious clones facilitates the development of recombinant viruses with improved therapeutic indexes to satisfy the criteria of safety and efficacy regulations. This review summarizes the current knowledge and strategies of genetic engineering for SVA, and addresses the current challenges and future directions of SVA as an oncolytic agent.